Etika dan Spiritualitas Guru Pendidikan Agama Kristen di Era Digital - Legi, Hendrik; Widiono, Gideon; Wamo, Antonius (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
The digital era has brought great changes in various aspects of life, including in the world of education. Christian Religious Education (PAK) teachers are required to not only master theological material, but also understand and integrate digital ethics and build a solid spirituality in the midst of cyber challenges. This article aims to examine the importance of ethics and spirituality in shaping the character of PAK teachers that are relevant to the needs of the times, as well as highlight the competencies that must be possessed in order to remain effective in educating the digital generation. Using the literature study method, this study examines theories about digital ethics, Christian spirituality, and educational principles based on the values of the Kingdom of God. The results of the study show that contemporary PAK teachers must be able to be role models in ethical behavior in virtual spaces, maintain integrity, respect digital rights, and live Christian values in every online activity. God's Word is the main basis for building ethical and spiritual sensitivity, as written in Romans 12:2 and Colossians 3:17. In addition, teachers are called to be light and salt in cyberspace, presenting a positive influence in the midst of information flows that are not always in accordance with Christian values. Through good digital competence, character strengthening, and deep spirituality, PAK teachers in the digital era are expected to shape students to become responsible, faithful, and integrity digital citizens. This research enriches the theoretical study of the role of Christian teachers in 21st century education.AbstrakEra digital telah membawa perubahan besar dalam berbagai aspek kehidupan, termasuk dalam dunia pendidikan. Guru Pendidikan Agama Kristen (PAK) dituntut untuk tidak hanya menguasai materi teologi, tetapi juga memahami dan mengintegrasikan etika digital serta membangun spiritualitas yang kokoh di tengah tantangan dunia maya. Artikel ini bertujuan untuk mengkaji pentingnya etika dan spiritualitas dalam membentuk karakter guru PAK yang relevan dengan kebutuhan zaman, serta menyoroti kompetensi yang harus dimiliki agar tetap efektif dalam mendidik generasi digital. Dengan menggunakan metode studi literatur, penelitian ini mengkaji teori-teori tentang etika digital, spiritualitas Kristen, serta prinsip-prinsip pendidikan berbasis nilai-nilai Kerajaan Allah. Hasil kajian menunjukkan bahwa guru PAK kekinian harus mampu menjadi teladan dalam perilaku etis di ruang virtual, menjaga integritas, menghargai hak digital, serta menghidupi nilai-nilai Kristiani dalam setiap aktivitas daring. Firman Tuhan menjadi dasar utama dalam membangun kepekaan etis dan spiritualitas, sebagaimana tertulis dalam Roma 12:2 dan Kolose 3:17. Selain itu, guru dipanggil untuk menjadi terang dan garam di dunia maya, menghadirkan pengaruh positif di tengah arus informasi yang tidak selalu sesuai dengan nilai-nilai kekristenan. Melalui kompetensi digital yang baik, penguatan karakter, dan spiritualitas yang mendalam, guru PAK di era digital diharapkan dapat membentuk peserta didik menjadi warga digital yang bertanggung jawab, beriman, dan berintegritas. Penelitian ini memperkaya kajian teoretis tentang peran guru Kristen dalam pendidikan abad ke-21.